TINJAUAN YURIDIS PENETAPAN PENGADILAN TENTANG DISPENSASI KAWIN (STUDI KASUS PENETAPAN PENGADILAN AGAMA BANTUL NOMOR 0023/Pdt.P/2009/PA.Btl dan 0067/Pdt.P/2009/PA.Btl) - , SENI DESIANTI MAULIDA; , Prof. Dr. Abdul Ghofur Anshori, S.H., M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
This study is aimed to know the process of appeal submission in married dispensation, to know the consideration from the judge in giving determination of married dispensation, besides it also to know the law effect about a marriage under the merit age limit. This is a Juridical Empirical Law study which done to get the primary data in the field, and also the other matter which related to this research as the secondary data. Primary data get from books/literature to explain the primary law matter. The method and data collector in this thesis is done by library research and interview. The result of the study analyzed in the way of descriptive qualitative. The result of this study shows that the process of appeal submission of marriage dispensation is the dispensation appeal attached by companion letter from or known by the village chief or the head of official village at that place. After get the companion letter, the applicant comes to the court and brings the written applicant then submit the letter applicant and registered to clerk of court in the court. The determination of married dispensation Number: 0023/Pdt.P/2009/PA.Btl. The judge fulfill the request of determination married dispensation seen from the benefit side, if the marriage do not arranged quickly it is afraid if there are some acts that collide with the religion norm and the existing rule. The determination of married dispensation appeal Number: 0067/Pdt.P/2009/PA.Btl the judge refuses the appeal because it is contradiction with Article 53 paragraph (1) and (2) Compilation of Islamic Law. The effect is divorce because the physic is not mature yet to build the household, and the law effect is that the couple status becomes legal then appears the right and the obligation of wife-husband.